Mexican state-labor relations and the political implications of free trade. - COOK, Maria Lorena (1995)
Reviews the declining position of labour in the 1980s, and discusses some recent developments and possible emerging trends in state-labour relations under the Salinas administration. Examines likely political implications of NAFTA for Mexican trade unions and their future relations with the state.